Clarifying the Interrelations of Residents' Perceived Tourism-Related Stress, Stressors, and Impacts. (January 2021) - Jordan, Evan J.; Lesar, Laura; Spencer, Daniel M.
While stress has recently been documented as an adverse impact of tourism, it has not been examined alongside traditional tourism impacts to determine their similarities and differences. To clarify the interrelations of these phenomena, we explored whether tourism-related stressors were similar to well-known tourism impacts, and whether perceived tourism impacts increased the likelihood of experiencing tourism-related stress. Residents of O'ahu, Hawai'i, were asked how much tourism impacted them on 36 variables, whether tourism caused them stress, and if so, how. Study findings reveal that tourism-related stressors often correspond with what have been traditionally considered tourism impacts. Moreover, only five of the tourism impact variables predicted the experience of tourism-related stress, and of these only one was a frequently cited stressor. Connecting impacts to stressors expands the possibility that certain tourism impacts could have consequences that go beyond mere opinions and attitudes, as stress has many health and wellness consequences.